Ensino e aprendizagens de Botânica direcionados para a realidade de uma comunidade extrativista Amazônica - (:unkn) unknown (Brasil, 2025)
The present academic production has as its theme “The teaching of Botany in the context of an Amazonian extractive reserve” and its objective is to contribute to the improvement of teaching and learning of Botany in the final years of Elementary and High School, in a school located in a community extractivist activities in the Amazon, through the adaptation and contextualization of the content with local reality and knowledge. The choice of Escola Estadual Professora Maria Mendes Simões as a field of study was due to its location in the Rio Cajari Extractive Reserve, where natural wealth contrasts with educational and socioeconomic challenges. The research shows that the teaching of Botany in Basic Education aims to provide students with an in-depth understanding of plants, their vital processes and their ecological importance. The teaching of Botany at Escola Estadual Professora Maria Mendes Simões is being partially influenced by the educational and environmental context of the Amazonian extractive community in which it is located. This is noticeable by the approach that, although it is based on scientific concepts, still lacks greater connection with the local reality and the Amazon flora, limiting the application of knowledge in students' daily practice. However, as a possibility of bringing Botany content even closer to local daily life, in order to produce better results in the community's teaching-learning, we highlight the importance of integrating the curriculum with projects that involve direct observation of local plants, active participation in environmental preservation activities and the development of practical experiences, such as the study of sustainable flora management techniques.
Keywords: Ensino Básico; Basic Education; Biologia; Biology; Botânica; Botany; Escola do Campo; Country school; Prática educativa; Educational practice; CNPQ::CIENCIAS BIOLOGICAS